Korallipteris, a new genus for Mesozoic Gleichenia-like fern fronds - Vera, Ezequiel Ignacio (2012)
A new morphogenus, Korallipteris, is proposed to accommodate fertile or sterile fern fronds possessing essentially Gleichenia-like morphology (e.g., pinnate fronds with small pecopteroid pinnules) but lacking diagnostic features that allow their classification at fern family-level. The aim is thus, to solve an old nomenclatural problem that involves the use of illegitimate genera, such as Gleichenites Goeppert and Microphyllopteris Arber. Several species of Gleichenites described from the Mesozoic of Argentina and Chile, and Microphyllopteris unisora Cantrill and Nagalingum from Antarctica are here reassigned to Korallipteris gen. nov. The proposal of Nagalingum and Cantrill to preserve Gleicheniaceaephyllum Crabtree emend. Nagalingum and Cantrill for true Gleicheniaceous ferns, diagnosed by having an arrested laminar bud, is here accepted.